Astragaloside IV: An Effective Drug for the Treatment of Cardiovascular Diseases - Tan YQ; Chen HW; Li J (Dove Medical Press, 2020)
Yu-Qing Tan,1,2 Heng-Wen Chen,1,* Jun Li1,* 1Department of Cardiology, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing 100053, People’s Republic of China; 2Graduate School of Beijing University of Chinese Medicine, Beijing University of Chinese Medicine, Beijing 100029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Heng-Wen Chen; Jun Li Email chenhengwen@163.com; 13051458913@163.comAbstract: Cardiovascular disease (CVD), the number one cause of death worldwide, has always been the focus of clinical and scientific research. Due to the high number of deaths each year, it is essential to find alternative therapies that are safe and effective with minimal side effects. Traditional Chinese medicine (TCM) has a long history of significant impact on the treatment of CVDs. The mode of action of natural active ingredients of drugs and the development of new drugs are currently hot topics in research on TCM. Astragalus membranaceus is a commonly used Chinese medicinal herb. Previous studies have shown that Astragalus membranaceus has anti-tumor properties and can regulate metabolism, enhance immunity, and strengthen the heart. Astragaloside IV (AS-IV) is the active ingredient of Astragalus membranaceus, which has a prominent role in cardiovascular diseases. AS-IV can protect against ischemic and hypoxic myocardial cell injury, inhibit myocardial hypertrophy and myocardial fibrosis, enhance myocardial contractility, improve diastolic dysfunction, alleviate vascular endothelial dysfunction, and promote angiogenesis. It can also regulate blood glucose and blood lipid levels and reduce the risk of cardiovascular diseases. In this paper, the mechanism of AS-IV intervention in cardiovascular diseases in recent years is reviewed in order to provide a reference for future research and new drug development.Keywords: Astragalus membranaceus, astragaloside IV, traditional Chinese medicine, cardiovascular diseases, cardiomyocytes